Reducing underage alcohol and tobacco use: Evidence from the introduction of vertical identification cards - Andriana Bellou; Rachana Bhatt (Institute for the Study of Labor (IZA), 2012)
From 1994-2009, forty-three states changed the design of their driver's license/state identification cards in an effort to reduce underage access to and consumption of alcohol and tobacco. In these states, individuals under the age of 21 are issued licenses that are vertically oriented, whereas licenses for individuals 21 and older retain a traditional horizontal shape. This paper examines the effect of this design change on underage alcohol and tobacco use. Using a difference-in-difference methodology, we find a reduction in drinking and smoking for 16 year olds. These results are robust to the inclusion of state-specific linear time trends, and are upheld in a triple difference model that uses a within state control group of teens that did not receive a vertical license to control for state-specific unobserved factors. Interestingly, we find that the effects of the design change are concentrated in the 1-2 years after a state begins issuing vertical licenses; there is little evidence of an effect of the license on underage consumption in the long-run. This finding is consistent with a scenario where, over time, teens substitute towards other methods of obtaining age-restricted products, and/or retailers continue to make underage sales.
Keywords: I1; J1; 330; youth alcohol and tobacco policies; Jugendschutz; Alkoholkonsum; Rauchen; Zutrittskontrolle; USA